2014
DOI: 10.3389/fnbeh.2014.00259
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of social behavior by the agouti pigmentation gene

Abstract: Agouti is a secreted neuropeptide that acts as an endogenous antagonist of melanocortin receptors. Mice and rats lacking agouti (called non-agouti) have dark fur due to a disinhibition of melanocortin signaling and pigment deposition in the hair follicle. Non-agouti animals have also been reported to exhibit altered behavior, despite no evidence for the expression of agouti outside the skin. Here we confirm that non-agouti mice show altered social behavior and uncover expression of agouti in the preputial glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The 10 th top region was centered on agouti signaling protein (ASIP), a well-known gene influencing pigmentation in mammals [ 66 , 67 ], that has a lesser known role in inhibiting lipolysis [ 68 ]. More recently, evidence is emerging that variation at ASIP can influence social behavior, most likely through its antagonistic effects on melanocortin receptors or α-melanocortin stimulating hormone [ 69 , 70 ]. Other than a small, predicted gene of unknown function, LYST is the only gene in the 30 th region.…”
Section: Resultsmentioning
confidence: 99%
“…The 10 th top region was centered on agouti signaling protein (ASIP), a well-known gene influencing pigmentation in mammals [ 66 , 67 ], that has a lesser known role in inhibiting lipolysis [ 68 ]. More recently, evidence is emerging that variation at ASIP can influence social behavior, most likely through its antagonistic effects on melanocortin receptors or α-melanocortin stimulating hormone [ 69 , 70 ]. Other than a small, predicted gene of unknown function, LYST is the only gene in the 30 th region.…”
Section: Resultsmentioning
confidence: 99%
“…; Carola et al. ). Melanistic individuals tend to be more resistant to stress, more aggressive, and more sexually active (reviewed in Ducrest et al.…”
Section: Introductionmentioning
confidence: 98%
“…Recent work has shown that some color polymorphisms are associated with extensive pleiotropic effects, creating substantial variation in life-history strategies among alternative phenotypes. For example, melanistic coloration is associated with variation in a suite of physiological and behavioral traits potentially through pleiotropy in the melanocortin system (Morgan and Cone 2006;Ducrest et al 2008;Carola et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…C57BL/6, CBA/J and BALB/c mice showed significant changes between their control and stressed groups in all behavioral indexes, and C57BL/6 mice displayed a much higher decrease in locomotor activity, climbing response and immobility time than the other two strains in the open-field test and forced swim test. These results are partly consistent with a study by Valeria Carola et al ., who observed that non-agouti mice with dark fur exhibited decreased locomotion and more aggressive-like behavior compared to agouti mice with light fur [ 39 ].…”
Section: Discussionmentioning
confidence: 99%